Clinical relevance of masks in the operating room? A systematic review. (November 2021) - Burdick, Halie N.; Maibach, Howard
Highlights: Face masks are recommended for sterile procedures, while data supporting this is lacking. Combining several of the studies favored not wearing a mask in prevention of surgical site infection. The results indicate no difference in surgical site infections between mask and maskless operations. Abstract: Background: Face masks are recommended for sterile procedures, while the data supporting this recommendation is lacking. Here we systematically review randomized control trials on mask efficacy in the operating room as a means to preventing surgical site clinical infection. Methods: PubMed, Google Scholar, Web of Science, and National Institute for Occupational Safety and Health Publications and Products were searched and articles were included if they fit the criteria of 1) randomized control trial, 2) clinical patient outcomes, 3) mask efficacy, 4) surgery setting, 5) in vivo, and 6) article was in English. Results: The results indicate no difference in surgical site infections between the operations where masks were worn versus the operations where no mask was worn. Conclusion: With such limited evidence and the great cost that accrues from purchasing face masks for all surgical staff, we hope for larger, well designed randomized control trials to evaluate the true clinical efficacy of surgical masks in the operating room.